AB0416 Early Good Eular Response Predicts Low/Remission Disease State in Rheumatoid Arthritis Patients on Treatment with Certolizumab in Real Life Settings. Data from Italian Registry Gisea. (9th June 2015) - Iannone, F.; Carlino, G.; Marchesoni, A.; Sarzi-Puttini, P.; Gorla, R.; Salaffi, F.; Foti, R.; Ferraccioli, G.; Salvarani, C.; Fusaro, E.; Ferri, C.; Paolazzi, G.; et al.
Abstract : Background: Identifying early predictors of sustained clinical response in patients with rheumatoid arthritis (RA) is a major challenge and would have substantial clinical and economic impact. Objectives: To evaluate the predicting value of a EULAR good clinical response at 3 months to reach Low Disease Activity (LDA)/Remission in RA patients treated with certolizumab in a standard of care setting. Methods: Patients with RA treated with certolizumab because of their active disease included in the GISEA (Gruppo Italiano Studio Early Arthritis) register were prospectively analysed. The first endpoint of this study was to assess the value of 3 a months good EULAR clinical response to predict a LDA, 28-joints Disease Activity Score (DAS28) ≤3.2 or disease remission (DAS28 <2.6) at 6-12 months. Moreover, the baseline factors that might predict the 3 months EULAR good response therapy were also evaluated. Results: At entry, 278 patients (female 84%) had active disease (DAS28 5.1±1), age 54.8±12 years, mean duration of disease 9.8±8 years, and BMI 25.5±4 kg/m 2 . Certolizumab was given as first ever biological drug in 68% RA patients, and as ≥2 line biological treatment in 32%. The majority of the patients were also assuming glucocorticoids (77%) and 77% were on co-therapy with Disease Modifying Drugs (DMARDs). At 3 months, DAS28 significantly dropped at 4.01±1 and further decreased at 6 (3.2±1) and 12 (3.3±1) months, respectively (p<0.001). The percentage of patients achieving a good EULAR response was 52.1% at 3 months, 65.2% at 6 months, and 65.9% at 12 months. While patients attaining a state of LDA/disease remission were 51.5% at 6-12 months. The logistic multiple regression analysis (Table 1 ) showed that 1st line therapy was the only predictor (RR 6.7) of a good EULAR response, after adjustment for age, sex, disease duration, DAS28 at baseline. Furthermore, a good EULAR response at 3 months was the only strong positive predictor (RR 11.3) of LDA/DAS28 disease remission at 6-12 months, while the baseline DAS28 was negatively correlated (RR 0.31). Conclusions: This study provided evidence that, in the daily standard of care, RA patients on therapy with certolizumab achieving an early good EULAR response by 3 months maintain the good clinical outcome across 6-12 months, and predicts LDA/disease remission at 6-12 months. Disclosure of Interest: None declared